2019
DOI: 10.33594/000000092
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Grown Micro-Tissues for Cardiac Cell Replacement Therapy in Vivo

Abstract: This article is licensed under the Creative Commons Attribution-NonCommercial-NoDerivatives 4.0 International License (CC BY-NC-ND). Usage and distribution for commercial purposes as well as any distribution of modified material requires written permission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
(43 reference statements)
0
4
0
Order By: Relevance
“…For iPSC-CMs, it was reported that transplanted human iPSC-CMs could improve myocardial functions and alleviate ventricular remodeling in rat hearts ( Guan et al, 2020 ). Another study used iPSC-CMs and mesenchymal stem cells to generate micro-tissues for cardiac cell replacement therapy in vivo ( Sahito et al, 2019 ). These findings raised the possibilities that gene-edited patient-specific iPSC-CMs can be used as cell resources for intramyocardial transplantation to repair the structural or functional defect in FC patients.…”
Section: Discussionmentioning
confidence: 99%
“…For iPSC-CMs, it was reported that transplanted human iPSC-CMs could improve myocardial functions and alleviate ventricular remodeling in rat hearts ( Guan et al, 2020 ). Another study used iPSC-CMs and mesenchymal stem cells to generate micro-tissues for cardiac cell replacement therapy in vivo ( Sahito et al, 2019 ). These findings raised the possibilities that gene-edited patient-specific iPSC-CMs can be used as cell resources for intramyocardial transplantation to repair the structural or functional defect in FC patients.…”
Section: Discussionmentioning
confidence: 99%
“…The cells were cultured in complete DMEM (4.5 g) glucose l −1 with 15% fetal calf serum (FCS) (Sigma-Aldrich, Taufkirchen, Germany). MSCs were prepared as described previously [8] and cultured in complete DMEM containing (1 g) glucose l −1 (Thermo Fisher Scientific) and 15% FCS. For a generation of miPS-CMs, TαP4 [28] cultivated on mitomycin inactivated embryonic feeder cells in Iscove's modified Dulbecco's medium (IMDM) supplemented with 15% FCS and 1000 units ml −1 leukemia inhibitory factor (ORF Genetics, Reykjavik, Iceland).…”
Section: Cell Culture and Generation Of Mips Cell-derived Cmsmentioning
confidence: 99%
“…Although 2D cultures can be used to address uncounted scientific questions the interaction of cells in a 3D environment opens new avenues in many applications. In cardiac cell therapy, it was shown early that single PSC-derived CMs (PSC-CMs) hardly engraft in the diseased murine tissue while the addition of connective tissue cells substantially enhances the cell engraftment in vitro and in vivo [2,8,9]. Based on such findings, we have developed a simple method of generating microtissues from mesenchymal stem cells (MSCs) and murine iPSC-CMs (miPSC-CMs) resulting in >10-fold enhanced early engraftment of PSC-CMs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation